Estimating the Technical Efficiency of Smallholder Cocoa Farmers in Malaysia - Fadzim, Wan Roshidah; Aziz, Mukhriz Izraf Azman; Mat, Siti Hadijah Che; Maamor, Selamah (International Journal of Economics and Financial Issues, 2016)
In Malaysia, cocoa production is characterized by several problems that lead to low productivity. The low productivity is evident from the continuous drop in cocoa production since 2001 despite efforts from governing bodies to boost output. This study investigates this issue by looking into the production efficiency among smallholder cocoa farmers in Malaysia. The technical efficiencies of cocoa farmers in Malaysia is estimated using data envelopment analysis. The study relies upon primary data gathered during the 2013 production season. Data are collected from a set of structured questionnaire administered on 375 smallholder cocoa farmers throughout Malaysia. Result of the analysis shows that the mean efficiency score is 0.526. In short, there existed inefficiency among the sampled farmers. Keywords: Cocoa, technical efficiency, data envelopment analysis JEL Classifications: D24, Q12